Certificate Presenting Charles Lathrop Parsons Award to Glenn Seaborg - American Chemical Society (1964)
Presented for outstanding public service by a member of the American Chemical Society.
Keywords: Seaborg, Glenn T. (Glenn Theodore), 1912-1999; U.S. Atomic Energy Commission; University of California, Berkeley; American Chemical Society; Nobel Prize winners